Prevention of unintentional injury in children. Issue 9 (September 2017) - Patel, David; Magnusen, Eliza; Sandell, Julian M.
Abstract: Unintentional injuries are one of the leading causes of mortality and morbidity in children, many of these injuries can be anticipated and avoided. There is mounting evidence for the effectiveness of injury prevention interventions, but further research and data are needed to help identify the reason for inequalities between population groups and to identify the full scale of the problem. This article outlines the different approaches to injury prevention and discusses primary, secondary and tertiary prevention along with the 6 E's: Education, Enforcement, Engineering, Environment, Economics and Empowering. It outlines some of the current government legislation, national policies, strategies and interventions. Health professionals who work with children have a professional responsibility to keep them safe from harm. They can do so by identifying children at risk, providing safety advice and signposting parents to further educational or practical resources, and by further spreading awareness amongst colleagues.